2008
DOI: 10.1111/j.1743-6109.2008.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Genital Responsiveness in Healthy Women With and Without Sexual Arousal Disorder

Abstract: Introduction Most pharmacological treatments that are currently being developed for women with sexual arousal disorder are aimed at remedying a vasculogenic deficit. Aim This study investigated whether pre- and postmenopausal women with sexual arousal disorder are less genitally responsive to visual sexual stimuli than pre- and postmenopausal women without sexual problems. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 31 publications
4
59
1
1
Order By: Relevance
“…The VPA response of women with subjective or combined symptoms (believed to constitute the majority of those who seek treatment) did not differ from those of a control group of women. Recently, Laan, van Driel, and van Lunsen (2008) evaluated whether women diagnosed with FSAD using DSM-IV criteria showed less genital response to visual sexual stimuli than a control group of women without sexual problems. They found no significant differences between the groups in VPA; however, women with FSAD reported less positive and slightly more negative affect in response to the erotic films.…”
Section: Criterion Amentioning
confidence: 99%
“…The VPA response of women with subjective or combined symptoms (believed to constitute the majority of those who seek treatment) did not differ from those of a control group of women. Recently, Laan, van Driel, and van Lunsen (2008) evaluated whether women diagnosed with FSAD using DSM-IV criteria showed less genital response to visual sexual stimuli than a control group of women without sexual problems. They found no significant differences between the groups in VPA; however, women with FSAD reported less positive and slightly more negative affect in response to the erotic films.…”
Section: Criterion Amentioning
confidence: 99%
“…Ultimately, therapy strives towards optimal sexual functioning, which is most often defined in terms of painless vaginal penetration. However, when taking into account a cognitive-motivational perspective, it becomes clear that interventions should not rely solely on CBT-related fear-reduction techniques, but optimally concentrate on the psychosocial meaning of sexual stimulation [20] by working on pain cognitions, sexual selfworth, context variables and motivational factors, always holding the interactive relationship component in mind.…”
Section: The Role Of Motives and Relational Processesmentioning
confidence: 99%
“…Other researchers welcome this merging due to unpractical and unworkable nature of DSM IV TR FSAD definition based on impaired/absent genital responses and the high overlap of the two problems (26). Impaired genital responsiveness was not found to be a valid diagnostic criteria in healthy women with or without sexual arousal disorder (17). Additionally the authors suggested that "desire not being triggered by any sexual/ erotic stimulus" should be considered as a primary or "must" criterion for diagnosis of SIAD as the diagnosis can only be made when sexual incentives are present or sufficient.…”
Section: Diagnostic Criteria For Substance-induced Sexual Dysfunctionmentioning
confidence: 99%
“…Diagnostic classification should be separately made for males and females as women's sexual responses may not be analogous to men. Additionally given the complexity of sexual responses in women, classifications based on simple linear sexual response cycle may not be (17,18). Sexual thoughts may act as an internal sexual stimuli and desire or arousal may be viewed as responses to this internal stimuli which implies that sexual desire is not spontaneous but rather a response to covert internal triggering processes (19).…”
Section: Diagnostic Criteria For Substance-induced Sexual Dysfunctionmentioning
confidence: 99%